Studies on botany and landscape history of abandoned grapeyards in the Northern Cserhát Hills, Hungary - Mravcsik, Zoltán; Harmos, Krisztián; Malatinszky, Ákos (JOURNAL OF LANDSCAPE ECOLOGY, 2009)
All abandoned grapeyards (altogether 12) of five villages in the Northern Cserhát Hills (Northern Hungarian Mountain Range) which carry enough relevant landscape historical features were observed. Within landscape history, grape management history of Nógrád county has been analysed as facing its conditions and processes in the Carpathian Basin. A comparison is given on national changes and local processes (areas of Kishartyán, Sóshartyán, Ságújfalu, Nógrádmegyer, Etes settlements). Every sample area is described and evaluated separately as well, thus, their differences and similarities can be observed. Altogether 252 vascular plant species were listed from the 12 grapeyards, 12 of which being protected (Linum tenuifolium, Linum hirsutum, Astragalus exscapus, Orchis militaris, Orchis purpurea, Orchis morio, Aster amellus, Adonis vernalis, Stipa pulcherrima, Jurinea mollis, Pulsatilla pratensis subsp. nigricans, Ornithogalum pyramidale) and 26 valuable at a local level. These abandoned grapeyards as semi-natural habitats are bases for secondary habitats, carrying several above mentioned values in the landscape formed by humans.
Keywords: abandoned grapeyard; nature conservation value categories; protected plants; Northern Cserhát; landscape history